Fabrication of Blood Capillary Models for Live Imaging Microarray Analysis - Muhammad Asri Abdul Sisak; Fiona Louis; Sun Hyeok Lee; Young-Tae Chang; Michiya Matsusaki (Micromachines, 2020)
Conventional microarray analysis usually deals with the monolayer or two-dimensional (2D) assays for the high-throughput screening applications. Even though these cell-based assays are effective for preliminary screening at least to have information on cytotoxicity, they do not adequately re-create the in vivo complexity of three-dimensional (3D) tissues. In this study, 3D-blood capillary models were constructed by using physiological collagen microfibers (CMF), which provide the extracellular matrix in the complex tissue. Micro-droplets of fibrin gels containing CMF, endothelial cells, and fibroblasts were cultured for five days in 48-wells plate to provide a medium-throughput system for screening applications. Blood capillaries networks were formed by optimizing the concentration of CMF used and the number of cells. Finally, this screening method was a powerful assay for the application on the selection of not only a specific chemical probe for blood capillary live-imaging, but also a drug, aptamer, and peptide with potential blood vessel targeting property.